Factors affecting the development of tourism human resources in Ba Ria - Vung Tau Province in the integration period - Ngo Thi My Hanh, Hanh (Technium Social Sciences Journal, 2023)
The article studies the factors affecting the quality of tourism human resources in Ba Ria - Vung Tau . The results show that the factors affecting the quality of human resources of tourism enterprises include: (1) Socio-economic environment, (2) Education, training and labor law. , (3) State support policies on labor, (4) Development of modern technology to support Ba Ria - Vung Tau province in the integration period, (5) Labor recruitment, (6) Analysis and evaluation of work results, (7) Working environment and labor relations, (8) Compensation and benefits Karma. On that basis, the authors propose solutions to improve the quality of human resources of tourism enterprises in Ba Ria - Vung Tau in the coming time.